PENYULUHAN DAN DETEKSI DINI FAKTOR RISIKO PENYAKIT TIDAK MENULAR PADA MASYARAKAT DESA HERO INO KECAMATAN TOBELO BARAT - Asih Blandina, Olivia; Nur Fitria, Pipit; Tjingaisa, Yurensi Felni; Yulianti Hohedu, Ribka; Veronika Ohoiwutun, Ludyana (HIRONO : Jurnal Pengabdian Masyarakat, 2021)
This community service was carried out for 1 day to the people of Hero Ino Village, West Tobelo District, which aims to increase the knowledge of the Hero Ino Village community about non-communicable diseases (PTM) and conduct health checks to detect uric acid, blood sugar and cholesterol levels early. This activity was carried out by a lecturer in the Nursing Study Program at Hein Namotemo University. The method used is counseling and health checks. The implementation stage begins with counseling about uric acid, cholesterol, and blood sugar diseases delivered by a lecturer in the Nursing study program at Hein Namotemo University, which is followed by discussions and questions and answers. Then proceed with a health examination which includes checking uric acid levels, blood sugar and cholesterol. The results of the evaluation of the health examination activities showed that the community of Hero Ino village had increased compared to before the counseling. The results of the health examination showed that the people of Hero Ino Village, West Tobelo District had high cholesterol levels as many as 12 people, high uric acid 15 people, and 1 person high blood sugar.